Development of Digital Competence of Vocational High School (SMK) Islamic Religious Education Teachers Within an Independent Curriculum Framework - Hodijah, Siti; Hermanto; Haryono, Pauzan (Proceeding International Conference on Education, 2023)
The use of a variety of new technologies in the learning process is getting stronger. The practice produces two general implications, positive and negative. This paper seeks to reveal the efforts of Islamic religious education teachers at the vocational high school level in increasing their digital competence amid the strengthening use of new technology in learning. This study uses a descriptive qualitative research method. The results of this study indicate that the development of teacher digital competence takes place through two stages. First, the stage of strengthening digital competence by following technical guidance on the management and use of ICT for Vocational High School (SMK) teachers develops it by self-learning through the use of YouTube, makes products in the form of Google Sites, and uses them in the learning process in class. Second, carry out post-guidance guidance programs for teachers and students at the school where the assignment is. The implications of the study are discussed within the framework of an independent curriculum. Practical advice for this study lies in the importance of integrating technical guidance, independent teacher learning, and collaboration between teachers as a basis for developing teacher competence.